Pengaruh Knowledge Management terhadap Pengembangan Sumber Daya Manusia dan Kinerja Karyawan Perhotelan di Sulawesi Selatan - Andi Hasbi (Jurnal Kawistara, 2020)
Many studies have linked knowledge management and human resource development to create standardized services. However, the relationship between the two in the hospitality industry is still lacking as an object of research. The purpose of this study was to analyze the influence of knowledge management on the development of hospitality HR in South Sulawesi. This research uses a quantitative approach with inferential statistical analysis. This research was conducted in three selected districts, namely, Bone Regency, Soppeng Regency, and Wajo Regency, which were the research locus. The population in this study were all-star and non-star hotel employees in the three districts. The total sample is 200 hotel employees and respondents are selected using the accidental method. Data collection using a questionnaire that was built based on previous research. The data analysis technique uses descriptive analysis and Structural Equation Modeling, which is processed in Linear Structural Relation software (LISREL 8.5). The results indicated that there was a significant influence on the development of human resources in hospitality. This means that to improve the outcome of hospitality HR including education, training and the development of the hospitality industry is required to be able to maintain and maintain knowledge management through the implementation of job procedures, able to transfer personal knowledge and technological mastery. Knowledge management directly has a little positive and significant impact on employee performance, but simultaneously Knowledge Management has a very positive and significant effect on employee performance through HR development. This research implies that performance-based training and development and application of knowledge management should be carried out simultaneously in the hospitality industry to produce standardized services in each district.Keywords: Employee Performance; Human Resource Development; Knowledge Management; Linear; Structural Equation Modeling; and Structural Relation software.